Protection of youth rights: the mandate of national human rights institutions in malaysia - Azhar, Alias; Yeon, Asmah Laili; Ayob, Zainal Amin; Arshad, Rozita
Malaysia introduced the Youth Societies and Youth Development Act 2007 (YSYDA 2007) and gazetted it in July 2007. It is an Act to facilitate the development of youth in Malaysia from the aspects of education, research, and human resource. Therefore, this paper examines the efforts of the Human Rights Commission of Malaysia (SUHAKAM) as a national human rights institution (NHRI), playing an important role in the mainstream efforts to ensure the protection and promotion of youth rights. This paper is a qualitative research paper in which it is more exploratory in nature and possibly leading to the development of concepts and theories. This paper presents the outcome of the historical and interview approaches as to find out how and why SUHAKAM has come to take its present form. In addition, this paper also summarises the efforts and roles played by SUHAKAM, pursuant to the protection of youth rights.